COMPARISION OF PERSONALITY TRAITS OF JUDO AND WRESTLING PLAYERS OF MAHARSHTRA (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the present investigation was to assess the personality traits of Judo and Wrestling payers Maharashtra. The study conducted on sixty samples, consisting of thirty Judo and thirty Wrestling players Maharashtra. Personality traits were obtained by administrating R. B. Cattell’s Sixteen Personality Factor questionnaire. The data collected through this test were analyzed with respect to personality traits i.e. extraversion, anxiety, tough poise, dependence and control. ‘T’ test was applied to compute the significance of differences among two groups. The significance of data was judged at .05 levels. The result of the study indicates that personality traits of Wrestling players and Judo players were different.